Radical ocean futures-scenario development using science fiction prototyping. (January 2018) - Merrie, Andrew; Keys, Patrick; Metian, Marc; Österblom, Henrik
Highlights: Applies the method of science fiction prototyping to the future of fisheries. Presents four 'radical' and compelling narrative scenarios. Each scenario is supported by a strong scientific evidence base. The scenarios account for complexity and non-linear change. Scenarios reflect interaction of ecological, technological & socio-economic change. Abstract: Scenarios can help individuals, communities, corporations and nations to develop a capacity for dealing with the unknown and unpredictable, or the unlikely but possible. A range of scientific methods for developing scenarios is available, but we argue that they have limited capacity to investigate complex social-ecological futures because: 1) non-linear change is rarely incorporated and: 2) they rarely involve co-evolutionary dynamics of integrated social-ecological systems. This manuscript intends to address these two concerns by applying the method of science fiction prototyping to developing scenarios for the future of global fisheries in a changing global ocean. We used an empirically informed background on existing and emerging trends in marine natural resource use and dynamics to develop four 'radical ocean futures, ' incorporating and extrapolating from existing environmental, technological, social and economic trends. We argue that the distinctive method as applied here can complement existing scenario methodologies and assist scientists in developing a holistic understanding of complex systems dynamics. The approach holds promise for making scenarios more accessible and interesting to non-academics and can be useful for developing proactive governance mechanisms.